KEMAMPUAN BERBICARA SISWA DALAM MENANGGAPI CARA PEMBACAAN CERPEN KELAS VIIA DAN VIIB SMPN 19 MUARA FAJAR PEKANBARU TAHUN AJARAN 2013/2014: (The Students' Ability to Speak in Response to the Reading of Short Stories at Seventh Grade Students of SMPN 19 Muara Fajar) - Saidat Dahlan; Supriyadi Supriyadi; Reniwati Reniwati (UIR Press, 2015)
Indonesian language has important and strategic role in the communication process in the middle of the association and social interaction. Through the Indonesian language is good and true, someone will be able to communicate both verbally and in writing to the other party in accordance with the context and situasi. Kemampuan speaking students well enough for the students' speaking style was influenced by the dialect of the native language. So the aim of this study was to determine the students' ability to speak in response to the reading of short stories seventh grade students of SMPN 19 Muara Fajar. The issues raised in this research is: how is the ability to speak the seventh grade students of SMPN 19 in response to the way Muara Fajar short story readings on aspects of pronunciation and intonation, how is the student's ability Muara Fajar SMPN 19 in response to a short story readings on suitability aspects of language? And how is the ability of students of class VII SMPN 19 Muara Fajar in response to a short story readings on aspects of mime and expression? The theory used is the theory Tarin, Nurgiantoro, Bungin, Sudjono, Suharma, Tri Endah Priyatni and Mustafa.populasi 147 people with a sample of 70 students selected at random. The method I use is descriptive quantitative method. To collect data the authors using observation and oral test. The conclusion of this study are: speech class VII SMPN 19 Muara Fajar in response to the reading of short stories academic year 2013/2014 on aspects of pronunciation categorized either with an average value of 77. The ability to speak the seventh grade students of SMPN 19 Muara Fajar in response to a short story readings on aspects suitability enough language category with an average of 62. the ability to speak the seventh grade students of SMPN 19 Muara Fajar in response to a short story readings on aspects of good gestures and expressions category with an average of 73. thus the hypothesis is rejected.